Validity and reliability of the KFORCE Sens® electrogoniometer in the evaluation of ankle, knee, and hip range of motion - Özüdoğru, Anıl; Canli, Mehmet; Kuzu, Şafak; Ceylan, İsmail; Alkan, Halil; Tuncay, Figen (University of Ghana College of Health Sciences, 2024)
Background: Range of motion (ROM) is essential for diagnosing limitations from musculoskeletal issues, developing treatment plans, and monitoring treatment progress. ROM assessments commonly involve tools like universal goniometers, evaluation scales, inclinometers, and smartphone applications. Objective: This study aimed to test the validity of the KFORCE Sens® electrogoniometer in evaluating lower extremity ROM by comparing it with the universal goniometer and examining the inter-rater and test-retest reliability. Methods: Fifty-one healthy volunteers (aged 18-25 years) were included in this study. The lower extremity ROM values of each participant were assessed by two assessors separately using a KFORCE Sens® electrogoniometer. The same assessors repeated the KFORCE Sens® electrogoniometer measurements once to examine test-retest reliability. Lower extremity ROM values were also assessed by one assessor using a universal goniometer. Results: According to the study findings, both the inter-rater and test-retest reliability of the KFORCE Sens® electrogoniometer device in all ROMs of the lower extremities were excellent (ICC > 0.80). In addition, the ROM values of the KFORCE Sens® electrogoniometer device and the ROM values of the universal goniometer in the same joint were highly correlated (r > 0.80, p < 0.05). Conclusion: The KFORCE Sens® electrogoniometer is a valid and reliable device for evaluating lower extremity ROM. © 2024 University of Ghana College of Health Sciences on behalf of HSI Journal. All rights reserved.
Keywords: electrogoniometers; lower extremity; Range of motion; reliability